2023
DOI: 10.3390/healthcare11101417
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis on Burnout Owing to Perfectionism in Elite Athletes Based on the Multidimensional Perfectionism Scale (MPS) and Athlete Burnout Questionnaire (ABQ)

Abstract: Previous studies have shown that burnout negatively affects athletes’ mental health. To further explore this subject, we conducted a systematic review and meta-analysis by combining data from previous studies. This study followed the PRISMA guidelines for systematic and reliable research and completed data extraction using 10 databases and 8 keywords in December 2021. There were 93 cases of initially extracted data from the selected articles (n = 14) and the meta-analysis was conducted using the “meta” package… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…Excluded studies involved study protocols and articles that did not investigate the relationship between perfectionism and athletic performance. These eight eligible studies included five systematic reviews ( 31 - 35 ) and three systematic review and meta-analysis studies ( 36 - 38 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Excluded studies involved study protocols and articles that did not investigate the relationship between perfectionism and athletic performance. These eight eligible studies included five systematic reviews ( 31 - 35 ) and three systematic review and meta-analysis studies ( 36 - 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…Athletes’ burnout is one of the carefully studied constructs in the light of perfectionism. In a recent meta-analytic research, Yang and colleagues have comprehensively reviewed the relationships between perfectionism and burnout in the athletic population ( 36 ). Their findings indicated that self-oriented perfectionism negatively influenced sports devaluation (SD), while socially prescribed perfectionism showed a positive impact on physical or emotional exhaustion and SD.…”
Section: Discussionmentioning
confidence: 99%